Implementasi Metode Luther untuk Pengembangan Media Pengenalan Tata Surya Berbasis Virtual Reality - Adhe Pandhu Dwi Prayogha; Mudafiq Riyan Pratama (Puslitbang Sinergis Asa Professional, 2020)
The purpose of virtual reality is to enable a motor and cognitive sensor activity ofsomeone in the artificial world created digitally to become imaginary, symbolic orsimulate certain aspects in the real world [1]. This technology is applied to the mediaintroduction of the solar system using the Luther method. The Luther Method consistsof 6 stages, namely Concept, Design, Material Collecting, Assembly, Testing, andDistribution. Luther method has advantages compared to other methods because thereare stages of material collecting which is an important stage in the development ofmultimedia and this Luther method can be done in parallel or can go back to theprevious stage [2]. At the Assembly stage the implementation uses the Unity Engineand Google VR SDK for Unity, the result is a virtual reality application that can displaythe solar system with 3-dimensional objects and an explanation is available on eachobject. While testing the blackbox on a variety of Android devices with differentspecifications. From the results of the application of the Luther method, it is verystructured and can run well in the development of multimedia applications, while theresults of testing, this Android-based virtual reality application cannot run on devicesthat do not have Gyroscope sensors and can run on devices with a minimumspecification of 1GB RAM will but the rendering process on 3D objects is slow.